A novel AB4-type RE–Mg–Ni–Al-based hydrogen storage alloy with high power for nickel-metal hydride batteries. (10th September 2019) - Wang, Wenfeng; Zhang, Lu; Rodríguez-Pérez, Ismael A.; Zhao, Yumeng; Liu, Xiaoxue; Zhang, Shuang; Guo, Wei; Ren, Kailiang; Li, Yuan; Han, Shumin
Abstract: La–Mg–Ni-based superlattice structure compounds are believed to be a promising negative electrode material with high power and superior hydrogen storage capacity for nickel-metal hydride batteries. They are built with [AB5 ] and [A2 B4 ] subunits, stacked along the c axis, with the following two sequences: one of rhombohedral and the other of hexagonal symmetry, called 3R and 2H, respectively. In this paper, we present the synthesis conditions and detailed structural characterization of rhombohedral La0.63 Nd0.16 Mg0.21 Ni3.53 Al0.11 with the AB4 -type structure. It is demonstrated that the AB4 phase is formed by a peritectic reaction between Pr5 Co19 -type (2H) phase and one liquid phase in a range of 1000–1010 °C. The compound exhibits a high discharge capacity of 391.2 mAh g −1 and can reach 286.2 mAh g −1 even at a discharge current of 1800 mA g −1 . The superior high rate dischargeability performance could be attributed to its preferable charge transfer rate and hydrogen diffusion speed. Furthermore, the cycling life of the AB4 compound is up to 83.3% after 200 cycles. As a result of these desirable electrochemical properties, the AB4 -type La–Mg–Ni-based compound with high power is considered to promote applications for high power battery materials. Highlights: The representative structures of 2H and 3R AB4 -type compounds are presented. Single AB4 -type La0.63 Nd0.16 Mg0.21 Ni3.53 Al0.11 compound is obtained. The AB4 -type phase is transformed by Pr5 Co19 through peritectic reaction. Single AB4 -type compound shows superior HRD 1800, achieving 286.2 mAh g −1 . Cycling stability of single AB4 -type compound is up to 83.3% at 200th cycle.